2021
DOI: 10.47216/literacytrek.932316
|View full text |Cite
|
Sign up to set email alerts
|

Violations of and threats to academic integrity in online English language teaching

Abstract: The move to online teaching has brought with it fresh opportunities for students to violate academic integrity. This paper considers such violations from within the domain of online English language teaching, although many of the ideas presented are applicable to other disciplines. The paper reports on a two-part study conducted at a university in Turkey. In the first part, qualitative data collected from students and staff through an online survey form were used to identify a new way of categorizing academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…This reason has a low percentage like the other three forms of academic dishonesty. This is in accordance with ÇeliK and Lancaster (2021), where students had a high level of attitude in online sessions compared to exam-realized violations and assignment-related violations. Threats that are a factor in academic dishonesty are online sessions that took a long time and are not monitored so that they feel they can leave their devices and do other activities.…”
Section: Online Session Related Violationsupporting
confidence: 89%
“…This reason has a low percentage like the other three forms of academic dishonesty. This is in accordance with ÇeliK and Lancaster (2021), where students had a high level of attitude in online sessions compared to exam-realized violations and assignment-related violations. Threats that are a factor in academic dishonesty are online sessions that took a long time and are not monitored so that they feel they can leave their devices and do other activities.…”
Section: Online Session Related Violationsupporting
confidence: 89%
“…Numerous research studies also claim that many high school graduates come from an academic background that hardly prepares them for university level work (Martin et al, 2012;Venezia & Jaeger, 2013) including developing skills on how to paraphrase and cite (Broeckelman-Post, 2009;Vieyra & Weaver, 2016) reference information sources (Gravett & Kinchin, 2020); understand what is considered to be academic misconduct (Bacha et al, 2012); and, how to avoid plagiarism (King & Brigham, 2018), among others. Instructional methods, course design and instructional delivery seem to have a significant influence on students to engage in academic integrity violation or not (Çelik & Lancaster, 2021;Orosz et al, 2015). Miller and Bartlett (2012) study reported that there is little agreement from teachers and between departments insofar as to which subject/ curriculum information and digital literacies should be taught at the secondary level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Valuable for our study is the interpretation of "academic culture" by Ö. Çelik and T. Lancaster (2021), by which they mean a system of values, norms, rules, patterns of behavior, modes of activity, principles of communication based on pedagogically adapted experience of scientific and cognitive activity. The cognitive level of scientific culture implies the availability of knowledge about the acceptable ways of cognitive activity in the research situation.…”
Section: Key Values Of the European Academic Culture Includementioning
confidence: 99%